Fluid/Structure Interactions - Semenov, Yuriy (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This Special Issue contains 12 papers devoted to fluid/structure interaction (FSI) problems. The main feature of the problems is an interface on which consistent boundary conditions for both the liquid and the solid regions are formulated. The presented studies cover a wide range of problems and methods for their solution, including problems of weak, or one-way interaction, in which the effect of interface deformation on the fluid flow can be neglected, as well as problems of the strong interaction, for which the interface change affects both the flow and the structure behaviour. The interest in FSI problems is very great due to their practical importance. Recent developments in engineering have led to advanced formulations of FSI problems. Some of them could not be formulated several years ago. The presented papers demonstrate progress in both numerical algorithms, mathematical apparatus and advanced computational techniques. In this issue, we have tried to collect different FSI problems, new mathematical and numerical approaches, new numerical techniques and, of course, new results, which can provide an insight into FSI processes.